EFEITO DA ADIÇÃO DE FARINHA DE CASCA DE UVA, OLIGOFRUTOSE E SUCO DE UVA (Vitis labrusca) NAS PROPRIEDADES FÍSICO-QUÍMICAS, REOLOGIA E FUNCIONALIDADE DE IOGURTE ORGÂNICO - Karnopp, Ariadne Roberto (2016)
The production of organic food is growing and these products are increasingly sought by consumers looking for healthy foods able to bring improvements to your health. Grape (Vitis spp.) is produced on a large scale worldwide and by-products generated from the processing can be used in the development of new products. The overall aim of this study was to develop an organic yogurt added with oligofructose, Bordeaux organic juice and skin grape (Vitis labrusca). For this, the work was divided in three chapters, one of literature review and two experimental chapters. Chapter 2 aimed to characterize the grape pomace and grape skin flours in relation to physical-chemical composition, content of bioactive compounds, reducing and antioxidant capabilities. Both the skin and grape flours showed a high insoluble fiber content (55.84 ± 0.63 and 51.02 ± 1.12 g / 100 g, respectively) higher value than 1900 mg of gallic acid equivalents (AGE) / 100 g total phenolic content, in which ortho-diphenols, flavonols, anthocyanins and water soluble tannins represent the major chemical markers. Regarding to functionality the grape pomace flour and grape skin flour showed values of 1373.64 ± 72.94 and 361.48 ± 2.99 mg AGE / 100 g in iron reduction capacity; 1574.26 ± 1499.79 ± 8.94 and 31.39 mg of ascorbic acid equivalents (AAE) / 100 g, the reduction of DPPH radical; and 2892.46 ± 61.69 and 426.34 ± 18.85 mg quercetin equivalent / 100 g total capacity reduction, respectively. The aim of Chapter 3 was to develop an organic yogurt added with grape juice, grape skin and oligofructose and evaluate its effects on the physicochemical, sensory and texture properties of yogurt and optimize the formulation according to their sensory, physicochemical and functional properties. Grape juice increases the viscosity and DPPH and TRC (total reducing compounds)content, grape skin increased the ash and total fibercontent and combined with oligofructose, skin increased firmness and consistency of yogurt. Using the desirability function to increase the average values of total reducing compounds, ash content, total fiber content and overall impression, a formulation containing 68% skin and 32% grape juice was indicated as optimal point of the experiment. This formulation showed values of 5.60 ± 0.13, 0.76 ± 0.02, 57.85 ± 1.36, 28.32 ± 2.10 and 7.09 ± 1.18 for the total fiber content (g / 100 g) ash content (g / 100 g), DPPH (AAE mg / 100g), CRT (GAE mg / 100 g) and overall impression, respectively. These results suggest that the grape pomace and skin from organic grape juice industry are promising for use in food industries and an interesting alternative to make available to consumers differentiated products with high added value.